Desenvolvimento de imunossensores microfluídicos descartáveis para detecção de biomarcadores visando o diagnóstico precoce da doença de Alzheimer - Oliveira, Tássia Regina de (Universidade Federal de São Carlos, 2019)
Alzheimer's disease (AD) is a neurodegenerative condition that affects a large number of elderly and has an important social and economic impact. In early stages, the AD diagnosis can significantly improve patients' quality of life. Currently, AD biomarkers require diagnostic imaging procedures that are expensive or invasive. Thus, methods less invasive that allow an early, fast, and low-cost diagnosis are highly desirable. For this reason, a disposable microfluidic device was developed based on electrochemical immunosensors for detection of the biomarkers A Disintegrin And Metalloprotease 10 (ADAM10) and amyloid-β peptide with 42 amino acids (Aβ42) in plasma and cerebrospinal fluid samples. Three elderly groups divided into cognitively healthy subjects, mild cognitive impairment (MCI), and AD patients at different disease stages were analyzed. For device construction, electrodes were screen printed on polyester foil using carbon and Ag/AgCl inks. Strategies for the biomarker’s detection were based on sandwich or competitive immunoassays. The horseradish peroxidase (HRP) enzyme was used as an electrochemical marker and responsible for the indirect response of the immunosensor. The ADAM10 calibration curve was linear in the range of 5.6 to 1.4 pg mL-1, with a linear correlation coefficient (r2) of 0.983, and a limit of detection (LD) of 5.6 fg mL-1. For βA42 biomarker, the concentration range was linear between 1.8 and 499.2 pg mL-1 of the peptide, with r2 = 0.977 and LD of 1.8 pg mL-1. Plasma samples from AD and MCI patients showed significantly increased of ADAM10 levels when compared with healthy subjects. Aβ42 concentrations found in the cerebrospinal fluid were statistically different between the control and the diseased groups. ADAM10 and its detection using the device proposed here proved to be a powerful tool for the early diagnosis and AD monitoring, which can bring great benefits to patients' quality of life.
Development of disposable microfluidic immunosensors for biomarker detection aiming early diagnosis of Alzheimer's disease
Keywords: Alzheimer's disease; Immunosensor; Microfluidic device; Early diagnosis; ADAM10; βA42; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA